DESA TANGGUH COVID-19: MELAKUKAN PROTEKSI SOSIAL DENGAN PARTISIPASI MASYARAKAT DESA PENGUJAN KABUPATEN BINTAN - Novi Winarti; Nur Aslamaturrahmah Dwi Putri; Ryan Anggria Pratama; Ardi Putra; Dewi Ayu Saputri (Fakultas Teknik, Universitas Bangka Belitung, 2022)
The existence of Corona Virus Diseases (Covid-19) has paralyzed various sectors of life, including the economic life of the community. Pengujan Village is one of the affected areas. During the covid-19 pandemic, the strength that comes from the community itself in the form of social capital is indispensable, but so far social capital in the form of community participation has been neglected. Social capital in the form of community participation is strengthened in order to realize social protection. Therefore, community service activities are carried out to the Pengujan Village community in carrying out social protection based on community participation. Community service activities are carried out through several stages, namely interviews and socialization. After the community service activities are carried out, the Pengujan Village community has the ability to improve the understanding and perspective of the Pengujan village community in exploring and utilizing existing social capital. The social capital explored is solidarity, network building and community participation. In the end, with good social capital, social protection slowly begins to take shape. Well-formed social protection then makes the Pengujan village a formidable village in the face of covid-19